Modeling the interaction among the Ukrainian and foreign stock markets - Lyashenko, S.V. (Економічний вісник Донбасу, 2010)
The interaction between Ukrainian stock market PFTS index, Russian stock market MICEX index, and Dow Jones (the United States of America) in the shortand long-term horizon was investigated in the study. Key words: stock market, indices, regression, vector autoregression, return.